Are People Ready for Personalized Brain Health? Perspectives of Research Participants in the Lifebrain Consortium. (4th November 2019) - Friedman, Barbara Bodorkos; Suri, Sana; Solé-Padullés, Cristina; Düzel, Sandra; Drevon, Christian A; Baaré, William F C; Bartrés-Faz, David; Fjell, Anders M; Johansen-Berg, Heidi; Madsen, Kathrine S; Nyberg, Lars; Penninx, Brenda W J H; et al.
Abstract: Background and Objectives: A healthy brain is central to physical and mental well-being. In this multi-site, qualitative study, we investigated views and attitudes of adult participants in brain research studies on the brain and personalized brain health as well as interest in maintaining a healthy brain. Design and Methods: We conducted individual interviews with 44 adult participants in brain research cohorts of the Lifebrain consortium in Spain, Norway, Germany, and the United Kingdom. The interviews were audio recorded, transcribed, and coded using a cross-country codebook. The interview data were analyzed using qualitative content analysis. Results: Most participants did not focus on their own brain health and expressed uncertainty regarding how to maintain it. Those actively focusing on brain health often picked one specific strategy like diet or memory training. The participants were interested in taking brain health tests to learn about their individual risk of developing brain diseases, and were willing to take measures to maintain their brain health if personalized follow-up was provided and the measures had proven impact. The participants were interested in more information on brain health. No differences in responses were identified between age groups, sex, or countries. Discussion and Implications: Concise, practical, personalized, and evidence-based information about the brain may promote brain health. Based on our findings, we have launched an ongoing global brain health survey to acquire more extensive, quantitative, and representative data on public perception of personalized brain health.